1999
DOI: 10.1074/jbc.274.22.15382
|View full text |Cite
|
Sign up to set email alerts
|

Domain Identification of Hormone-sensitive Lipase by Circular Dichroism and Fluorescence Spectroscopy, Limited Proteolysis, and Mass Spectrometry

Abstract: To analyze the structural domain composition of HSL in more detail, we applied biophysical methods. Denaturation of HSL was followed by circular dichroism measurements and fluorescence spectroscopy, revealing that the unfolding of HSL is a two-step event. Using limited proteolysis in combination with mass spectrometry, several proteolytic fragments of HSL were identified, including one corresponding exactly to the proposed N-terminal domain. Major cleavage sites were found in the predicted hinge region between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…In the case of cardiac troponin I (Morjana and Tal, 1998), the urea denaturation curves are biphasic, which indicates the presence of a stable folding intermediate, which might be related to the two-domain architecture of troponin I. Similar observations have suggested the presence of domains in the hormone-sensitive lipase (Osterlund et al, 1999) structure also.…”
Section: Guhcl/ureasupporting
confidence: 57%
“…In the case of cardiac troponin I (Morjana and Tal, 1998), the urea denaturation curves are biphasic, which indicates the presence of a stable folding intermediate, which might be related to the two-domain architecture of troponin I. Similar observations have suggested the presence of domains in the hormone-sensitive lipase (Osterlund et al, 1999) structure also.…”
Section: Guhcl/ureasupporting
confidence: 57%
“…Multiple potential transcription factor binding elements upstream of each transcriptional start site suggest the possibility of differential transcriptional regulation of HSL in different tissues and under various physiological conditions. According to the HSL domain structure model [the three-dimensional (3D) structure of the enzyme remains to be elucidated], the enzyme can be subdivided into three functional regions (41)(42)(43)(44). The N-terminal domain (amino acids 1-300) is believed to mediate enzyme dimerization (45) and interaction with FABP4, a fatty acid binding protein known to enhance HSL enzyme activity (46)(47)(48).…”
Section: Hsl Enzymologymentioning
confidence: 99%
“…The C-terminal portion of HSL displays secondary structural homology with that of acetylcholinesterase and several fungal lipases (5) and bacterial brefeldin A esterase (6), consisting of parallel ␤-sheets flanked by ␣-helical connections, which has allowed these proteins to be classified as ␣/␤-hydrolases (7). Using limited proteolysis, it has been suggested that HSL is composed of two major structural domains (8,9). Based on sequence alignment, structural homology with fungal lipases, and mutational analyses, the C-terminal domain has been shown to contain the catalytic triad and other residues important in hydrolytic activity, as well as a 150-amino acid insert that has been termed the regulatory module because several serines located within this region have been shown to be phosphorylated (1,10).…”
mentioning
confidence: 99%
“…Based on sequence alignment, structural homology with fungal lipases, and mutational analyses, the C-terminal domain has been shown to contain the catalytic triad and other residues important in hydrolytic activity, as well as a 150-amino acid insert that has been termed the regulatory module because several serines located within this region have been shown to be phosphorylated (1,10). The N-terminal domain in rat HSL constitutes the first 323 amino acids, which are encoded by exons 1-4, and displays no sequence or structural similarity with any other known proteins (8,9).…”
mentioning
confidence: 99%